Artie and pink marsh : two novels - George, Ade (University of Chicago Press, 1963)
The novel captures the character and lively vernacular speech of a young Loop office worker in a series of sketches first developed in Ade's feature column in the Chicago Record, "Stories of the Streets and of the Town."